Bulk and high-energy ball-milled Gd5Si2Ge2: Comparative study of magnetic and magnetocaloric properties - do Couto, Giselle Giovanna [UNESP]; Svitlyk, Volodymyr; Jafelicci, Miguel [UNESP]; Mozharivskyj, Yurij (Elsevier B.V., 2011)
High-energy ball milling was employed to produce small particles of Gd5Si2Ge2. Magnetic and magnetocaloric properties of the ball-milled and bulk Gd5Si2Ge2 samples were investigated through the magnetization measurements. When compared to the bulk material, a significant decrease in saturation magnetization and magnetocaloric effect (-Delta S-max = 4 vs. 20 J/kgK for Delta H = 0-5 T) is observed even after the relatively short ball milling time of 4 h which produced particles with an average size of ca. 0.5 mu m. The ball-milled samples appear to loose a first-order structural transition, present in bulk Gd5Si2Ge2, and display a superparamagnetic behaviour below the corresponding Curie temperatures. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Magnetic properties; Magnetocaloric properties; Ball milling; Structural transition